2001
DOI: 10.1046/j.1365-2362.2001.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐inflammatory cytokines in patients with essential hypertension

Abstract: Patients with EH have an altered profile of pro-and anti-inflammatory cytokines, consistent with monocyte activation in the circulation. The importance of these changes for the pathogenesis of EH and/or its secondary complications remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
1
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 30 publications
(48 reference statements)
4
86
1
3
Order By: Relevance
“…Similar disagreements was also observed in studies of human hypertensives, which showed increased circulating levels of IL-1β in one study and decreased levels in another (Dalekos et al, 1997;Dalekos et al, 1996;Peeters et al, 2001). It has been suggested that genetic differences in study populations may account for the variability where these differences are the cause of differences in cytokine expression and are wholly a characteristic of hypertension.…”
Section: Discussionsupporting
confidence: 60%
“…Similar disagreements was also observed in studies of human hypertensives, which showed increased circulating levels of IL-1β in one study and decreased levels in another (Dalekos et al, 1997;Dalekos et al, 1996;Peeters et al, 2001). It has been suggested that genetic differences in study populations may account for the variability where these differences are the cause of differences in cytokine expression and are wholly a characteristic of hypertension.…”
Section: Discussionsupporting
confidence: 60%
“…48 Similar observations have been made in hypertensive patients. 49 Our important new finding was that treatment with PNU-282987 did not reduce blood pressure but decreased the levels of these inflammatory factors in SHR tissues in most cases and greatly attenuated EOD as assessed by both light and electron microscopy. Thus, pharmacological rescue of the deficit in ␣7nAChR signaling in SHRs has anti-inflammatory effects.…”
Section: Et Al ␣7nachr and Hypertensive Organ Damage 303mentioning
confidence: 83%
“…Since the interaction in the risk for EH of one allele of the HLA system (a key element of the immune response) and an infectious agent (C. pneumoniae) has been described in our study, the probability that immune and inflammatory mechanisms are important factors in the pathogenesis of EH (as has been well documented in atherosclerosis at the cellular 21 and biochemical level 22 ) is clearly higher than that previously suspected. On the basis of several experimental findings, [23][24][25][26][27][28] it has been hypothesized that chronic C. pneumoniae infection of the vessels may induce a chronic immune response orchestrated by cytokines and mediated by reactive oxygen intermediates. This may result in increased vascular resistance and lead to increased blood pressure.…”
Section: Discussionmentioning
confidence: 99%